Thermodynamic entropy as a marker of high‐cycle fatigue damage accumulation: Example for normalized SAE 1045 steel. Issue 12 (19th July 2020) - Teng, Zhenjie; Wu, Haoran; Boller, Christian; Starke, Peter
Abstract: A nondestructive thermographic methodology is utilized to determine the fracture fatigue entropy for evaluating the fatigue damage in metals within the high‐cycle fatigue regime. Thermodynamic entropy is shown to play an important role in the fatigue process to trace the fatigue damage as an irreversible degradation of a metallic material being subjected to cyclic elastic‐plastic loading. This paper presents a method to evaluate fatigue damage in the normalized SAE 1045 steel being based on the concept of thermodynamic entropy and its nonlinearities. The procedure looks to be applicable to constant and load increase tests proven by experiments.